Becky with the Twitter: Lemonade, social media, and embodied academic fandom. Issue 2 (3rd April 2019) - Patrick, Stephanie
ABSTRACT: As someone who uses Twitter to follow celebrity culture, but rarely tweets directly 'at' celebrities, I have been neglected in much work on social media that centres on issues of authenticity or 'democratisation'. In this article I theorise 'aca-fandom' in relation to race, situating myself as a white feminist researcher/consumer of Black women's cultural and intellectual production. I reflect upon on my own use of Twitter in relation to Beyoncé's star image in order to explicate ways of engaging with celebrity beyond the authenticity paradigm centring on a front-stage/back-stage dichotomy. By following prominent social justice activists and writers who comprise 'Black Twitter', I was able to access their commentary on Lemonade in ways that enriched my understanding of Beyoncé's work; work that I increasingly felt distanced from, but more enthralled by. This article uses autoethnographic methods to re-centre the researcher body and illuminate connections between privilege and perspective on both star–audience relations and subject–researcher positions. Although Twitter may not challenge the hierarchical structures of media production, nor necessarily provide more 'authentic' views on celebrity, it does provide access to diverse perspectives on celebrity texts and, in this way, is a valuable resource for both audiences and researchers of celebrity culture.